IgG-NMO status after vitamin D supplementation in patients with NMOSD: a case report and a review of literature - Shaygannejad, Vahid; Mirmosayyeb, Omid; Askari, Gholamreza; Maracy, Mohammad Reza; Maljaie, Mohammad Bagher; Saraf-Bank, Sahar (Progress in Nutrition, 2018)
Introduction: Neuromyelitis optica Spectrum Disorder (NMOSD) is an inflammatory disorder of the CNS that presents typically with relapses of optic neuritis or transverse myelitis, in which IgG autoantibodies against aquaporin-4 water channel protein probably play a pathogenic role. We presented two cases who newly diagnosed with NMOSD that presented alterations in IgG-NMO status after vitamin D supplementation. Case presentation: We reported 2 cases, a 36-year-old female and a 27-year-old male newly diagnosed with NMOSD. Cases were stable in remission and experienced no attack and none of them didn’t take pulse therapy in the previous 3 months. Vitamin D level and IgG-NMO titration in 36-year-old female were 21 ng/dl and 1/320, and in 27-years-old male were 29 ng/dl 1/100, respectively. As their prescription, they took 50000 IU of vitamin D3 per week for 15 weeks. After 15 weeks vitamin D level raised in both of them and IgG-NMO titration was negative in cases. Conclusion: We reported 2 cases with high titration of IgG-NMO whom IgG-NMO status altered after high dose of vitamin D supplementation. Physiological variation in vitamin D may apply a major impact on autoimmune and inflammatory diseases. Further studies with larger sample sizes need to prove these results.